Delay Time Reduction in VCSELs by Optimizing Laser Parameters - Hisham, Hisham K. (Iraqi Journal for Electrical and Electronic Engineering, 2017)
An extensive analysis on reducing the turn-on time delay (t on ) in vertical cavity surface emitting lasers (VCSELs) has conducted successfully by considering all the recombination rate coefficients R(N) Besides the R(N) coefficients, the impact of other laser parameters such as, injection current (I inj ), laser cavity volume (V),mirror reflectivity (R), and operating temperature (T) also have investigated. Unlike pervious studies, the temperature dependence (TD) of t on is calculated according to TD of laser parameters instead of well-known Pankove relationship. Results showed that, t on can be reduced by increasing the I inj and/or the N i . Meanwhile, the t on increases by increasing the R(N) coefficients. Also, results showed that the t on can be reduced by increasing the R-level or by optimizing laser cavity volume.